Late-onset neonatal sepsis in Suzhou, China - Tao Pan; Qiujiao Zhu; Pei Li; Jun Hua; Xing Feng (BMC, 2020)
Abstract Background This study aimed to describe the causative organisms of neonatal late-onset sepsis (LOS) and their antimicrobial resistance in Suzhou, Southeast China over a 7-year period. Methods We performed a retrospective study on neonates with LOS from Jan1, 2011 to Dec 31, 2017. The demographic, clinical, and laboratory data of neonates with LOS were analyzed. Logistic regression was used to investigate the risk factors with mortality. Results During the study period, 202 neonates with LOS were finally identified. The most common pathogens were Escherichia coli (29.2%), followed by Klebsiella pneumoniae (19.3%), and Coagulase-negative Staphylococcus (CoNS) (16.8%). Nearly 90% of the K. pneumoniae were resistant to cefazolin and 71.8% to ceftazidime. Thirty-four patients (16.8%) died. Multivariable logistic regression showed that significant predictors of mortality were birth weight < 1500 g, respiratory distress and convulsions. Conclusions Gram-negative organisms have an important role in LOS in our region, with high levels of resistance to third-generation cephalosporins. These data may help in the selection of antibiotics for empirical treatment of neonates with sepsis.